Economic Valuation of Mangrove Ecosystem at Gerung District, West Lombok Regency - Mufti Petala Patria; Siti Dian Rosadi; Nisyawati Nisyawati (HAYATI Journal of Biosciences, 2021)
Research regarding economic valuation of mangrove in Gerung District, West Lombok Regency has been conducted. The purposes of this research were to calculate and analyze economic value from mangrove ecosystem at Gerung District. Research methods used observation and interviews. Direct Economic Value (DEV) were obtained from direct use of mangrove with a value IDR. 227,040,000/year. Indirect Economic Value (IEV)were calculated from mangrove ecosystem services with a value IDR. 1,405,041,200/year, Existence Value (EV) was obtained by Contingent Valuation Method (CVM) with a value IDR. 1,520,000/year. Option Value (OV) were calculated from biodiversity value with a value were IDR. 1,200,000/year. Total Economic Value (TEV) of mangrove in Gerung District were IDR. 1,634,801,200/year.